Isotopic Fractionation of Oxygen and Carbon in Lime Mortar Under Natural Environmental Conditions. Issue 3 (18th July 2016) - van Strydonck, Mark J Y; Dupas, Michel; Keppens, Edward
Abstract : The rate of calcite formation and the isotopic fractionation in lime mortar during the process of mortar setting were examined. The diffusion rate of atmospheric CO2 in the sample is the rate-controlling step of the chemical reaction. A Rayleigh diffusion in the mortar causes an enrichment of 13 C and 18 O in the samples.